2014
DOI: 10.1186/1880-6805-33-6
|View full text |Cite
|
Sign up to set email alerts
|

The physiological and psychological relaxing effects of viewing rose flowers in office workers

Abstract: BackgroundIn recent years, the physiological relaxing effect brought by nature is becoming clear; however, many workers find it difficult to be exposed to nature in their working environment. Exposure to fresh flowers represents an opportunity to incorporate nature into their working lives. In this study, we examined the effects of exposure to roses on physiological and psychological variables (heart rate variability, pulse rate, and subjective responses) in office workers.ResultsThe experimental site was Mizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 20 publications
10
74
1
3
Order By: Relevance
“…Olfactory stimulation by Japanese cypress leaf oil and inhalation of D-limonene enhanced parasympathetic nervous activity by 34.5 and 26.4 %, respectively, compared with a control (air) [5,6]; these findings were in accordance with the results of our previous laboratory experiments [17,18]. In our forest therapy field experiment, which included a large sample size of 625 participants [19], 79.2 % of the participants showed an increase in parasympathetic nervous activity in a forest environment compared with that in an urban environment.…”
Section: Resultssupporting
confidence: 82%
“…Olfactory stimulation by Japanese cypress leaf oil and inhalation of D-limonene enhanced parasympathetic nervous activity by 34.5 and 26.4 %, respectively, compared with a control (air) [5,6]; these findings were in accordance with the results of our previous laboratory experiments [17,18]. In our forest therapy field experiment, which included a large sample size of 625 participants [19], 79.2 % of the participants showed an increase in parasympathetic nervous activity in a forest environment compared with that in an urban environment.…”
Section: Resultssupporting
confidence: 82%
“…Recent studies have focused on the physiological relaxing effects of nature-derived stimulation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and there are several reports on the effects of wood odor on humans [9][10][11]. Miyazaki et al [9] reported that inhalation of Taiwan hinoki oil odor decreases systolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that natural environments or nature-derived stimuli, such as forests [36][37][38][39][40][41][42], urban parks [43][44][45], flowers [46][47][48][49][50], and foliage plants [51,52], induce physiological relaxation in humans. Wood is a familiar natural material which we have many opportunities to touch on a daily basis, and it is used for many household objects, such as interior materials of buildings and houses, furniture (desks and shelves), and stationery.…”
Section: Discussionmentioning
confidence: 99%